La controversia sobre la vivisección - Álvarez-Díaz, Jorge Alberto (Acta Bioethica, 2007)
The paper reviews the vivisection in nonhuman animals and whether it is justifiable nowadays from a bioethical point of view. The work departs with a brief historical perspective about the animal vivisection topic until the new outbreak of the controversy in the twentieth century. It reflects on the ethics of the relation between human otherwise, it would be contrary to ethics.